Variasi Ketebalan Arang Cangkang Biji Karet dengan Metode Filtrasi Downflow Dalam Penurunan Parameter Fe Air Tanah Dalam - Andri Rhomadon Ritonga; Marhadi Marhadi (Jurnal Daur Lingkungan, 2019)
Water resources generally cover surface and ground water. Surface water will be more easily polluted than ground water, because surface water is more easily contaminated with sources of pollution so that people use water sourced from deep ground water.  In Jambi city particular the Kenali Asam Atas area, is included in a residential area with a moderate density of approximately ± 6,903 Ha. PDAM service area coverage is still 2%, from the service area coverage of 10965 SR. The purpose of this study was to reduce Fe and pH parameters in deep groundwater using downflow and aeration filtration methods on variations in thickness of rubber seed shell charcoal by filtration method and variation of processing time in the aeration process using bubble aerator. The results of the downflow filtration method using variations in the thickness of 15 cm and 30 cm rubber seed shell charcoal for Fe parameters of 0.302 mg / l and pH of 5.08, while in the aeration treatment process using a variation of processing time of 30 minutes and 60 minutes for Fe parameters amounting to 0.354 mg / l and pH of 5.23.